IPTEKS PENGENDALIAN INTERNAL TERHADAP ASET TETAP PADA PT JASA RAHARJA (PERSERO) CABANG SULAWESI UTARA - Herawati, Elly; Mokoginta, Rachaya M.; Datu, Christian (Universitas Sam Ratulangi, 2018)
PT JASA RAHARJA (Persero) branch North Sulawesi is a branch office from PT JASA RAHARJA (Persero) and this company is one of state-owned enterprises which engaged in social insurance, especially for accident insurance and compensation insurance. In running every operational activity, every company surely must have fixed assets, be it in the form of buildings, office equipment, vehicles and so which can support employee performance. Fixed asset in a company must be secured in many ways of surveillance, control over costs incurred to get the said fixed asset, provide asset number so it will be easier to review the useful life of each asset, and whether said asset still can support employees performance or not. In this case, it is very important for us to pay attention to its internal control, because based on a research we did during our internship in PT JASA RAHARJA (Persero) branch North Sulawesi, each asset’s internal control from the company need to be more efficient in terms of the element of the environment control, activities of control, related information on fixed asset and monitoring that has been done before to do physical matching of fixed asset, and appropriate allocation based on its function and responsibilities. Then, the company must pay attention to expenditures of income and expenses on fixed asset, by following insurance for fixed assets, make an audit committee, and implement the disposal and elimination of fixed asset. Suggestions for company to improve employees performance, through increasing exploration of knowledge and functions of application in order for employee to use it effectively and for presentation statement and efficiency of information about company’s fixed assets more reliable and accurate.Keyword : internal control, fixed asset, Insurance